Powerful Nuclear Outflows and Circumgalactic Medium Shocks Driven by the Most Luminous Known Obscured Quasar in the Universe - Andrey Vayner; Tanio Díaz-Santos; Peter R. M. Eisenhardt; Daniel Stern; Lee Armus; Daniel Anglés-Alcázar; Roberto J. Assef; Román Fernández Aranda; Andrew W. Blain; Hyunsung D. Jun; Chao-Wei Tsai; Niranjan Chandra Roy; et al. (The Astrophysical Journal)
We report integral field spectroscopy observations with the Near-Infrared Spectrograph on board the James Webb Space Telescope, targeting the 60 kpc environment surrounding the most luminous obscured quasar known at z = 4.6. We detect ionized gas filaments on 40 kpc scales connecting a network of merging galaxies, likely to form a cluster. We find regions of low ionization consistent with large-scale shock excitation surrounding the central dust-obscured quasar, out to distances nearly 8 times the effective stellar radius of the quasar host galaxy. In the nuclear region, we find an ionized outflow driven by the quasar with velocities reaching 13,000 km s ^−1 , one of the fastest discovered to date, with an outflow rate of 2000 M _⊙ yr ^−1 and a kinetic luminosity of 6 × 10 ^46 erg s ^−1 , resulting in a coupling efficiency between the bolometric luminosity of the quasar and the outflow of 5%. The kinetic luminosity of the outflow is sufficient to power the turbulent motion of the gas on galactic and circumgalactic scales, and is likely the primary driver of the radiative shocks on interstellar medium and circumgalactic medium scales. This provides compelling evidence supporting long-standing theoretical predictions that powerful quasar outflows are a main driver in regulating the heating and accretion rate of gas onto massive central cluster galaxies.